2018
DOI: 10.3329/bjpbg.v30i2.35528
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC DIVERSITY IN BAMBARA GROUNDNUT (Vigna subterranean) AS REVEALED BY MOLECULAR WEIGHTS OF THE SEEDS’ PROTEINS

Abstract: Nine accessions of Bambara groundnut (Vigna subterranea (L.) Verdc.,syn. Voandzeia subterranea (L.) Thouars ex DC.)  obtained from National Centre for Genetic Resources and Biotechnology (NACGRAB), Ibadan, Oyo state, were assessed for their genetic and phylogenetic relatedness through electrophoretic analysis of the seed proteins. 0.2g of the seeds were weighed and macerated with mortar and pestle in 0.2M phosphate buffer containing 0.133M of acid (NaH2PO4) and 0.067 of base (Na2HPO4) at pH 6.5. Protein charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Most of genetic diversity investigations documented high levels of genetic diversity among Bambara groundnut landraces sampled across large geographic regions 12 , 21 , 22 . Limited studies of the genetic structure of Bambara landraces have been conducted 21 , 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of genetic diversity investigations documented high levels of genetic diversity among Bambara groundnut landraces sampled across large geographic regions 12 , 21 , 22 . Limited studies of the genetic structure of Bambara landraces have been conducted 21 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The potential of this ‘miracle’ crop has not yet been explored to its full extent in South Africa, while Shegro et al 6 suggested that information on genetic variability among available local accessions (landraces) of Bambara groundnut can contribute to an improvement program in this country. Screening these Bambara landraces and the assessment of the genetic diversity of this poorly understood minor legume can provide breeders with genetic resources to assist with crop improvement including, yield, biotic and abiotic stress tolerance as well as the adaptability of the crop to various environments, which can contribute to the enhancement and maintenance of food security 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation